Estimation of impact location on concrete column. (25th April 2017) - Zhu, Junxiao; Ho, Siu Chun Michael; Kong, Qingzhao; Patil, Devendra; Mo, Yi-Lung; Song, Gangbing
Abstract: In this paper, an innovative method for real-time estimating impact location on concrete structures utilizing lead zirconate titanate (PZT) sensors is proposed. P -waves are a kind of stress waves excited by the impact events on concrete structures, and propagate in concrete structures with the information of the impact location. PZT sensors embedded in the concrete column were utilized to measure the P -waves and locate the impact locations with acceptable accuracy and precision. Experimental results have verified the effectiveness and the location accuracy for 15 simulated impact points on a model concrete column. Compared to existing methods, which rely on low energy acoustic emissions, the proposed method can detect high energy impulse events, typically resulting from impacts. Furthermore, the method is resistant against the effects of low frequency whole-structure vibrations introduced by the impact force. All of the above can be accomplished through a sparse array of sensors, which makes the method minimally intrusive.